2015
DOI: 10.1007/s13762-015-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic behavior and synergistic effect of nonthermal plasma and CuO/AC catalyst for benzene destruction

Abstract: Nonthermal plasma-catalysis hybrid technology (NTP-C) operated at ambient temperature and pressure offers an innovative and effective approach to solving the problem of dilute volatile organic compounds pollution. Herein, the destruction of benzene (50-450 ppm) over an in-plasma NTP-C composite system was investigated. The AO x /active carbon (AO x /AC), AO x /3A molecular sieve (AO x /MS), and AO x /c-Al 2 O 3 (A = Fe, Ag, Zn, Mn, and Cu) catalysts were prepared by the incipientwetness impregnation method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Fig.15presents the variation of RS at various voltages and RH using three processes at a fixed chloroform content obviously, the RS varies from 1.38 to 1.26 for RH when the RH varies from 5 to 90% and RS varies from 1.15 to 1.19 when input voltage varies from 9 to 21 kV, respectively. This synergistic effect is observed under different parameters and are in good agreement with those obtained by several groups[9,11,13,14,38].Figure16 shows that the increase of the relative humidity (90%) induces a decrease of the IBE of CO at each value of voltage injected. This decrease is more pronounced at 21kV: the IBE CO 64% at a RH of 90 %.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Fig.15presents the variation of RS at various voltages and RH using three processes at a fixed chloroform content obviously, the RS varies from 1.38 to 1.26 for RH when the RH varies from 5 to 90% and RS varies from 1.15 to 1.19 when input voltage varies from 9 to 21 kV, respectively. This synergistic effect is observed under different parameters and are in good agreement with those obtained by several groups[9,11,13,14,38].Figure16 shows that the increase of the relative humidity (90%) induces a decrease of the IBE of CO at each value of voltage injected. This decrease is more pronounced at 21kV: the IBE CO 64% at a RH of 90 %.…”
supporting
confidence: 88%
“…That could be explained by the fact that more electrons and reactive species (such as O • ) were formed and then leads to ozone production (Eqs. 9 and 10) [37,38]. .…”
Section: Injected Voltages Effectmentioning
confidence: 99%
“…As shown in Figure 2, the presence of packing materials in the discharge region maximizes the number of micro streamers and thus producing more high energy electrons [18]. These energetic electrons produce reactive intermediates resulting in increased VOC removal efficiency when compared to the unpacked reactors [57,73,74]. Surface discharges produced along the surface of the packing material may distribute the plasma more evenly and intensively throughout the reactor [75] and the catalytic reactions occur on the surface of the packing material.…”
Section: Packed Bed Reactorsmentioning
confidence: 99%
“…This is because porous alumina possess electron-accepting acidic center which acts as an adsorption material for compound with π-electrons [101]. He et al [73] reported that the activated carbon exhibits higher removal efficiency of benzene due to its higher surface area (S BET = 609.3 m 2 /g) when compared to other packing materials such as alumina (S BET = 230 m 2 /g) and molecular sieve (S BET = 45 m 2 /g).…”
Section: Surface Propertiesmentioning
confidence: 99%
“…6,7 Catalysts are identied to play an important role in further advancing the plasma-catalytic performance and energy efficiency of IPC system. 8 Heterogeneous catalysts have been employed for VOC decomposition, e.g., noble metals, 9,10 metal oxides, [11][12][13][14] and their combinations. [15][16][17][18][19][20][21] Among these catalysts, metal oxide catalysts (e.g., CoO x , 11 MnO x , 12 CuO 13 and CeO 2 14 ) attract tremendous interest in consideration of the high catalytic activity, good economics and superior poisoning resistance.…”
Section: Introductionmentioning
confidence: 99%